Answer:
The point was reflected over the y-axis.
The point was translated left 6 units
Explanation:
step 1
we know that
When you reflect a point across the y-axis, the y-coordinate remains the same, but the x-coordinate is transformed into its opposite
In this problem
If you apply a reflection across the y-axis
(x.y)------> (-x,y)
(3,-2) ------> (-3,-2)
step 2
If you apply a translation to the left 6 units
The rule of the translation is equal to
(x,y)------> (x-6,y)
(3,-2) ------> (3-6,-2) ----> (-3,-2)